2003
DOI: 10.1111/1467-7687.00289
|View full text |Cite
|
Sign up to set email alerts
|

The influence of language on theory of mind: a training study

Abstract: This study investigated the role of language in the development of theory of mind. It was hypothesized that the acquisition of the syntactic and semantic properties of sentential complements would facilitate the development of a representational theory of mind. Sixty preschoolers who failed false belief and sentential complement pretests were randomly assigned to training on false belief, sentential complements, or relative clauses (as a control group). All the children were post-tested on a set of different t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
270
0
14

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 374 publications
(300 citation statements)
references
References 51 publications
16
270
0
14
Order By: Relevance
“…Given these findings, it appears to be more plausible that children with ASD rely on the skill of complementation for verbal ToM performance rather than the other way around. Further research is needed to determine whether coaching of complement sentences may have benefits for false belief reasoning in individuals with ASD, along the lines of that which has been shown by training studies conducted with TD children (Hale & Tager-Flusberg, 2003;Lohmann & Tomasello, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Given these findings, it appears to be more plausible that children with ASD rely on the skill of complementation for verbal ToM performance rather than the other way around. Further research is needed to determine whether coaching of complement sentences may have benefits for false belief reasoning in individuals with ASD, along the lines of that which has been shown by training studies conducted with TD children (Hale & Tager-Flusberg, 2003;Lohmann & Tomasello, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…False belief understanding did not predict later memory for complements. Two training studies also support the hypothesised link between complement syntax and false belief task performance (Hale & Tager-Flusberg, 2003;Lohmann & Tomasello, 2003).…”
mentioning
confidence: 63%
“…Therefore, emotion language is not just a component of emotional competence; it is also a manifestation of 'theory of mind ' (ToM), the child's growing awareness of the existence of internal states in itself and in others (Harris, 1989 ;. Both cross-sectional (Dunn, Brown & Beardsale, 1991 ;Astington & Jenkins, 1999 ;de Villiers & de Villiers, 2000 ;Adriàn, Clemente, Villanueva & Rieffe, 2005;Astington & Baird, 2005) and training (Lohmann & Tomasello, 2003 ;Hale & Tager-Flusberg, 2003 ;Grazzani Gavazzi & Ornaghi, 2008) studies have shown that language plays a crucial role in fostering children's understanding of the mind (Milligan, Astington & Dack, 2007). Recent findings support the hypothesis of a bi-directional relationship between theory of mind and language (Slade & Ruffman, 2005) although the effect of language on theory of mind seems to be stronger than the other way round.…”
Section: Introductionmentioning
confidence: 90%